The Effect Of Parental Education Level Towards Student Biology Learning Achievement - Lubertus Abdi Widhyadi (Journal of Biological Science and Education, 2019)
Learning achievement is very important because, through achievement, the success of the teaching and learning process achieved by students can be seen. Learning outcomes and achievements obtained by children can not be separated from the role of parents, ranging from how to accompany while studying to use their knowledge to be transmitted to their children. The level of parental education is closely related to and it influences student learning outcomes and achievement. This study aims to study the effect of parental education on biology student achievement in class XI MIA in the South Konawe Regency. This type of research is correlational The population of this research is the XI MIA grade students of South Konawe District High Schools. The sample of this study was 221 students of class XI MIA. The research instrument used a questionnaire regarding the level of parental past education while learning achievement was obtained through the results of midterm tests of biology subjects. The analysis technique used regression analysis techniques. Based on the analysis results obtained a significant value (Sig.) 0.33 (α) 0.05. It can be concluded that the level of parental education (X) does not have a significant effect on student biology learning achievement (Y).Keywords: Parental Education, Learning Achievement